“De mulher para mulher”: uma análise discursivo-crítica da representação da identidade de Marisa Letícia em post publicitário das lojas Marisa (“From a woman to another”: a critical discourse analysis of Maria Leticia’s identity representation ...) - Gomes, Maria Carmen Aires; Garcia, Carolina Duarte (Estudos da Língua(gem), 2018)
Neste artigo, analisamos a forma pela qual os corpos e os discursos da ex-primeira dama Marisa Letícia e do ex-presidente Luís Inácio Lula da Silva e suas ações são socialmente produzidas em post publicitário. O corpus é constituído de um post que recontextualiza o depoimento do ex-presidente, ocorrido no dia 10/05/2017, e que foi veiculado no facebook no dia 11/05/2017 pela equipe de marketização das Lojas Marisa. Na análise, mobilizamos pressupostos da Análise do Discurso Textualmente Orientada (FAIRCLOUGH, 2001, 2003; CHOULIARAKI; FAIRCLOUGH, 1999) e discussões sobre performances de feminilidades (BUTLER, 2010). PALAVRAS-CHAVE: Análise do Discurso Crítica. Gênero. Recontextualização. Post publicitário. Performances. ABSTRACT In this article, we analyzed the way the bodies and the speeches by the former first lady Marisa Letícia and the former president Lula and their actions are socially produced through the discourse genre advertising post. The post was published on May 11th, 2017, by the Marisa Clothing Store marketing staff in its official Facebook page and it recontextualizes a social event: Lula’s testimonial, occurred on May 10, 2017, recontextualized through the following utterance: “if your mother is left without a gift, do not blame Marisa”. We mobilized theoretical-methodological reference of the the Textually Oriented Discourse Analysis (FAIRCLOUGH, 2001, 2003; CHOULIARAKI; FAIRCLOUGH, 1999) and by discussions on performances of feminilities (BUTLER, 2010). KEYWORDS: Critical Discourse Analysis. Genre. Recontextualization. Advertising Post. Performance.